Access to Justice : The English Experience with Small Claims - Baldwin, John (World Bank, Washington, DC, 2012)
The note reviews England's experience on the potential of small claims procedures in expanding access to justice, which allow legal redress in situations where formal litigation would be too costly. But, while these procedures offer access to justice, they also illustrate the difficulties that informal dispute resolution mechanisms can pose. Advantages of small claims procedures reveal that most lay litigants favor informal hearings over formal courts processes, losing parties are not required to pay the costs of the winning parties, and, by and large, judges seem to be willing, and able to adapt to the informality of small claims hearings. Difficulties however address the inadequacies of preliminary legal advice in the absence of relevant evidence, or witnesses, as well as the wide variations in judges' approaches, who expressed different attitudes in the application of ordinary law in small claims. Moreover, both the undefined role of lawyers in informal hearings, and ineffective enforcement of judgments remain unclear, and problematic. It is suggested that if greater access to justice is the objective, the key is to design a civil justice system that provides costs, and procedures, realistically, and proportionately to the issue in dispute.